2015
DOI: 10.1007/s40726-015-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Metal Pollution in Coastal Sediments

Abstract: Coastal sediment is a vital habitat for aquatic and marine life in coastal ecosystem. However, urbanization and economic development in coastal areas have resulted in environmental problems globally. Due to coastal development such as new industrial facilities and commercial port expansion, anthropogenic metals are introduced to the adjacent areas. Therefore, metal pollution in coastal areas is one of the focused environmental concerns. Sediment quality in coastal zone reflects the long-term environmental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 78 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…Industrial activities (e.g. tannery, foundry or paper processing) can release trace metals wastewaters contaminating the coastal areas and causing a massive ecological impact on water organisms (Qian et al, 2015). Trace metals are also introduced into estuarine and coastal zones from nonpoint sources through aeolian and/or alluvial processes for example atmospheric transport, underground waters, rivers, run-off and ocean outfalls (Chester, 1990;Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial activities (e.g. tannery, foundry or paper processing) can release trace metals wastewaters contaminating the coastal areas and causing a massive ecological impact on water organisms (Qian et al, 2015). Trace metals are also introduced into estuarine and coastal zones from nonpoint sources through aeolian and/or alluvial processes for example atmospheric transport, underground waters, rivers, run-off and ocean outfalls (Chester, 1990;Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A comparsion made with that of the world river sediment average value indicated in Martin and Meybeck(1979) (See Table 2) revealed that concentrations of Cr in three sampled sites (S3, S8, and S10) and Pb at two sampled sites (S4 and S6) were exceeded the World River Sediment Average Value. This implies that the sediments at these sites were highly enriched which may be due to varying amount of local inputs, sources and other environmental factors influencing metal concentration (Qian et al, 2015). The concentrations of Cd in the sediment at all samples sites surpass the World River Sediment Average Value, exhibiting elevated concentration of Cd in Little Akaki River sediment.…”
Section: Concentration Of Heavy Metals In Little Akaki River Sedimentmentioning
confidence: 86%
“…A comparison made with that of the world river sediment average value indicated in Martin and Meybeck (1979) (See Table 2) revealed that concentrations of Cr in three sampled sites (S3, S8, and S10) and Pb at two sampled sites (S4 and S6) exceeded the world river sediment average value. This implies that the sediments at these sites were highly enriched which may be due to varying amounts of local inputs, sources and other environmental factors influencing metal concentration (Qian et al 2015). The concentrations of Cd in the sediment at all sampling sites surpass the world river sediment average value exhibiting an elevated concentration of Cd in Little Akaki River sediment.…”
Section: Concentration Of Heavy Metals In Little Akaki River Sedimentmentioning
confidence: 86%